Performance of newly employed trainee accountants in Gauteng, South Africa, versus the skills expectations of employers: How big is the gap?. Issue 5 (October 2019) - Kunz, Rolien; de Jager, Herman
The objective of this article is to determine whether the professional skills demonstrated by newly employed first-year trainee accountants (i.e. their performance) meet the expectations of audit managers and, if they do not, to determine the size of the expectation–performance gap. A questionnaire was used to determine the expectations and the perceptions of the actual capabilities of trainee accountants among South African audit managers at large audit firms in Gauteng. The findings revealed that newly employed first-year trainee accountants did not meet audit managers' expectations, with their expectations always exceeding their perceptions of performance. The professional skill with the largest expectation–performance gap was the ability to take responsibility for one's own development (37.9%) and that with the smallest gap was the ability to display honesty and integrity (9.4%).